Photocatalytic Surface Modification of PI Film for Electroless Copper Plating - Wenxia Zhao; Zenglin Wang; Liang Qiao; Shiwei Liu; Hongjian Zhao; Yani Yan (Advances in Condensed Matter Physics)
This study investigated the surface modification of polyimide (PI) film through TiO2 photocatalytic treatment. The effects of TiO2 content, treatment duration, and UV power on the surface topography, surface contact angle, and adhesion strength of the surface-modified PI films were investigated. The results indicated that, after surface modification under the optimal photocatalytic conditions, the surface contact angle of the PI film decreased from 84.4° to 38.8°, and the adhesion strength between the PI film and the electroless copper film reached 0.78 kN/m. X-ray photoelectron spectroscopy analysis further demonstrated that carboxyl groups formed on the surface of the PI film after photocatalytic treatment. The surface hydrophilicity and adhesion strength of the surface-modified PI film were enhanced due to the numerous carboxyl groups formed on its surface. Therefore, the photocatalytic treatment is an environmentally friendly and effective method for the surface modification of PI films.